Meanings and uses of public spaces for the homeless. A study in Valparaíso and Viña del Mar - Berroeta, Héctor; Muñoz, María Isabel (Revista de Psicología, 2013)
From a qualitative study, based on in-depth interviews, self- report inventories and behavioral mapping, spatial significances attributed by homeless people are ascribed to the public spaces in the cities of Viña del Mar and Valparaíso. The results expose the main characteristics referred to the public space, their patterns of use, action modes and the spatial significance connected to the experiences of the trajectory in street. The entailment with the public space is articulated into a background of exclusion-threat and freedom appreciation, forcing tactic deployments which institute an answered public space.